Dynamic linear adsorption with solid adsorbent material - Poliakov, V.L. (Доповіді НАН України, 2021)
A mathematical problem of linear physical adsorption of a dissolved impurity is formulated, by consider-ing its diffusion transfer during the filtration of an aqueous suspension through a uniform adsorbent bed at a constant rate. By averaging the impurity concentrations in the free and bound states over an arbi-trary time period, an approximate solution of the problem is obtained, which is only expressed in terms of the elementary functions. On its basis, it is proposed to calculate the rational duration of the filter run. The solution is discussed and illustrated with a number of examples with typical input data. Сформульовано математичну задачу лінійної фізичної адсорбції розчиненого домішку з урахуванням його дифузійного переносу разом з фільтрацією водної суспензії через однорідний шар адсорбенту з постійною швидкістю. Завдяки осередненню концентрацій домішків у вільному і фіксованому зв’язаному станах протягом довільного періоду часу одержано наближений розв’язок задачі, який виражається тільки через елементарні функції. На його основі пропонується розраховувати раціональну тривалість фільтроциклу. Розв’язок обговорюється і ілюструється рядом прикладів з типовими вихідними даними.